Standard Costing System - a management tool by deviations - Simeonova, R. (Економічний вісник Донбасу, 2016)
Standard Costing System nowadays serves as a reliable tool to control and manage production costs. This article studies the theoretical and practical-applied aspects related to its use. The different types of standard cost are examined and a model for applying it is developed. Particular attention is paid to the deviations in the Standard Costing System, and these are classified according to their nature. Formulas for analysis of the deviations are proposed. Their application is illustrated with suitable examples. The importance of standard prices and some difficulties relating to their use is shown.